The dietary practices of hypertensive adults admitted to the cardiology department at Deido District Hospital in Cameroon - Nyangono Biyegue Christine Fernande; Mintom Medjo Pierre; Nnang Ebanda Veronique; Ngondi Judith Laure (Advances in Food Technology and Nutrition Sciences, 2024)
Objective To assess the dietary habits of patients suffering from hypertension in Cameroon in the context of nutrition transition (Nutrition transition is the shift in dietary consumption and energy expenditure that coincides with economic, demographic, and epidemio logical changes. Specifically, the term is used for the transition of developing countries from traditional diets high in cereal and fiber to more Western pattern diets high in sugars, fat, and animal-source food). Methodology A cross-sectional descriptive study was carried out during six months on 206 hypertensive patients attending the Deido district hospital. BMI was calculated using body weight and height. Hypertension was defined as the 2017 ACC/AHA guidelines (SBP ≥ 130 mmHg, or DBP ≥ 80 mmHg). Eating habits and food consumption score were assessed by using Food Questionnaire validated by the Laboratory of Nutrition and Nutritional Biochemistry (University of Yaounde 1, Cameroon). Food mineral contents were also evaluated. Results Patients suffering from hypertension consumed all groups of food as fruits (pawpaw, avocado, pineapple, water melon and or ange), vegetables (folong, okok and carrots), tubers (plantains, cassava, unripe banana and yam), cereals (rice and white bread), legumes (egusi, beans and groundnuts), fats (margarine and refined palm oil), spices (onion and garlic) and animal proteins (fish, red meat, milk, eggs and dairy products). Results of consuming foods rich in micronutrients revealed that hypertensive patients mostly eat foods rich in sodium. The food consumption score is limit means that the global quality diet is inadequate quality and adequate quantity. Conclusion Patients suffering from hypertension have inadequate quality of diet and most consume foods rich in sodium.